Management and 1‐Year Outcomes of Patients With Newly Diagnosed Atrial Fibrillation and Chronic Kidney Disease: Results From the Prospective GARFIELD‐AF Registry - Goto, Shinya (J Am Heart Assoc, 2019)
BACKGROUND: Using data from the GARFIELD‐AF (Global Anticoagulant Registry in the FIELD–Atrial Fibrillation), we evaluated the impact of chronic kidney disease (CKD) stage on clinical outcomes in patients with newly diagnosed atrial fibrillation (AF). METHODS AND RESULTS: GARFIELD‐AF is a prospective registry of patients from 35 countries, including patients from Asia (China, India, Japan, Singapore, South Korea, and Thailand). Consecutive patients enrolled (2013–2016) were classified with no, mild, or moderate‐to‐severe CKD, based on the National Kidney Foundation's Kidney Disease Outcomes Quality Initiative guidelines. Data on CKD status and outcomes were available for 33 024 of 34 854 patients (including 9491 patients from Asia); 10.9% (n=3613) had moderate‐to‐severe CKD, 16.9% (n=5595) mild CKD, and 72.1% (n=23 816) no CKD. The use of oral anticoagulants was influenced by stroke risk (ie, post hoc assessment of CHA (2) DS (2)‐VASc score), but not by CKD stage. The quality of anticoagulant control with vitamin K antagonists did not differ with CKD stage. After adjusting for baseline characteristics and antithrombotic use, both mild and moderate‐to‐severe CKD were independent risk factors for all‐cause mortality. Moderate‐to‐severe CKD was independently associated with a higher risk of stroke/systemic embolism, major bleeding, new‐onset acute coronary syndrome, and new or worsening heart failure. The impact of moderate‐to‐severe CKD on mortality was significantly greater in patients from Asia than the rest of the world (P=0.001). CONCLUSIONS: In GARFIELD‐AF, moderate‐to‐severe CKD was independently associated with stroke/systemic embolism, major bleeding, and mortality. The effect of moderate‐to‐severe CKD on mortality was even greater in patients from Asia than the rest of the world. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01090362.